IN MEMORY OF THE SCHOLAR - Кобзева О. П. (TARIXIY TADQIQOTLAR, 2026)
The article highlights the life and scholarly activity of the outstanding Uzbek orientalist, archaeologist, and historian, Academician A.R. Mukhammedjanov. It demonstrates his contribution to the study of the ancient and medieval history of Uzbekistan, the training of young researchers, and the development of textbooks for secondary and higher education institutions.